anti-ER+ breast cancer by activating endoplasmic reticulum stress to induce apoptosis - YUAN Lie; YUAN Lie; ZHOU Weiying; ZHOU Weiying; ZHOU Duanfang; ZHOU Duanfang (陆军军医大学学报, 2023)
Objective To investigate the mechanism of celastrol (Cel) against estrogen receptor positive (ER+) breast cancer by activating endoplasmic reticulum stress-mediated apoptosis. Methods ER+ human breast cancer cell lines MCF-7 and T47D were used as research objects. MTT assay was used to detect the effect of Cel on cell viability. Western blotting were employed to detect the expression of apoptosis-related proteins. RT-qPCR and Western blotting were applied to measure the expression of endoplasmic reticulum stress-related molecules at mRNA and protein levels. A nude mouse model of orthotopic transplantation of MCF-7 cells was established to observe the effect of Cel on the growth of transplanted tumors. Results MTT Results showed that Cel inhibited the viability of MCF-7 and T47D cells in a dose-dependent manner (P < 0.05). Western blotting showed that Cel up-regulated the expression of apoptosis-related proteins, Cleaved PARP and BAX, and down-regulated the expression of BCL-2 (P < 0.05). RT-qPCR indicated that Cel up-regulated the mRNA levels of endoplasmic reticulum stress-related genes IRE1α, ATF6, PERK, ATF4, CHOP and BIP (P < 0.05). Western blotting revealed that Cel treatment resulted in increased expression levels of endoplasmic reticulum stress marker BIP, of PERK pathway related proteins p-PERK, p-eIF2α, ATF4 and CHOP, of IRE1α pathway associated proteins p-IRE1α and XBP1s, and of ATF6 pathway associated protein Cleared ATF6. In vivo experiment Results showed that Cel significantly reduced the volume of orthotopic transplanted tumor in nude mice (P < 0.05), and had no significant effect on their body weight. Conclusion Cel has a certain inhibitory effect on the proliferation of ER+ breast cancer MCF-7 and T47D cells, and its mechanism may be related to the activation of endoplasmic reticulum stress signaling pathway to induce apoptosis.